2022
DOI: 10.1021/acs.analchem.2c04117
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Based Highly Sensitive Assay of Circulating MicroRNAs for Early Prediction of the Response to Neoadjuvant Chemotherapy in Breast Cancer

Abstract: The response to neoadjuvant chemotherapy (NAC) is highly correlated with survival in breast cancer (BC) patients. The early prediction of the response to NAC could facilitate treatment adjustments on a patient-by-patient basis, which would improve patient outcomes and survival. Conventional techniques used for detecting circulating microRNAs (miRNAs), which act as biomarkers for the early prediction of NAC efficacy in BC patients, are associated with limitations such as low sensitivity and specificity. We desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Overall, nine studies (60%) [ 26 , 28 , 55 , 56 , 58 , 59 , 60 , 62 , 63 ] received a “low ROB”, four studies (27%) [ 57 , 61 , 65 , 66 ] were assigned an “unclear ROB” rating, and two studies (13%) [ 54 , 64 ] were assigned a “high ROB”. The omission of appropriate statistical analysis for predicting model validation and information in the first three domains (i.e., participants, predictors, and outcome) was a frequent source of bias in terms of high and unclear judgment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, nine studies (60%) [ 26 , 28 , 55 , 56 , 58 , 59 , 60 , 62 , 63 ] received a “low ROB”, four studies (27%) [ 57 , 61 , 65 , 66 ] were assigned an “unclear ROB” rating, and two studies (13%) [ 54 , 64 ] were assigned a “high ROB”. The omission of appropriate statistical analysis for predicting model validation and information in the first three domains (i.e., participants, predictors, and outcome) was a frequent source of bias in terms of high and unclear judgment.…”
Section: Resultsmentioning
confidence: 99%
“…We did not assess publication bias with funnel plot analysis since our meta-analysis included a maximum of nine studies, and the inclusion of fewer than ten studies may not provide enough power to test the real asymmetry [ 68 ]. Stevic 2018 [ 56 ], McGuire 2020 [ 54 ], Li 2022 [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors used this method to assess the expression levels of three circulating miRNAs, such as miR-21, miR-155, and miR-195, in a BC cohort treated with NAC. They showed that miRNA levels seemed to distinguish the NAC-responder patients from those non-responders [ 49 ]. Another method carried out to improve the standard qRT-PCR technique for miRNA quantitative analysis is the branched rolling circle amplification (BRCA).…”
Section: Bc and C-mirnasmentioning
confidence: 99%
“…However, low sensitivity and low specificity of detection techniques limit miRNA analysis, and new methods are under development. Li and colleagues, for instance, devised a new graphene oxide (GO)-based qRT-PCR method for detecting miRNAs and distinguishing NACT responders in eBC patients [186]. Further results are needed to better understand how miRNA may become useful for patient stratification and for defining personalized treatment in eBC.…”
Section: Non-coding Rnas: Mirna and Circrnamentioning
confidence: 99%